A scientometric review of the scientific literature on child effects on adults: Topics of interest and areas for development in psychological research - Eleni Kalogirou; Edouard Gentaz (Acta Psychologica)
Considerable effort has been devoted to understanding how parents influence child development. Less attention has been given to the effects that children exert on their parents. This review aims to systematically survey the links between scientific articles exploring this question. Results of a document co-citation analysis reveal that research on this topic has been scarce and primarily concerned by how child and adolescent disruptive behaviour negatively impacts parents. Academic attention is directed to research that conceptualizes child effects as the outcome of genetic or temperamental predispositions. The implications of such a constrained view of child influence are discussed, highlighting the need for applied research on how children can actively contribute to positive behavioural change in parents and other adults.